The use behaviour of pregnancy health information among the teen expectant mothers - Ruzegea, Mboni Amiri (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2014)
Teenage pregnancy is a globalpublic health concern linked to higher morbidity and mortality for mothers and unborn babies. This study investigated pregnancy health information use behaviour of teen expectant mothers (TEMs)in public antenatal care (ANC) clinics in Tanzaniato make informed decisions during pregnancy and ascertained the barriers they faced in the process. Ittested the first hypothesis that demographic and self-efficacy factors are responsible for TEMs' PHI use behaviour patterns using a representative sample (n= 150). The study relied on a self-developed pregnancy health information use questionnaire (PHIU-Q) to collect data from TEMs in three major ANC clinics in Temeke, Dar as salaam. The baseline survey revealed uneven PHI use behaviour patterns among the respondents due tomany PHI use aspects relevant for making informed decisions: reasons for use (PHI need), awareness, knowledge, sources, preference, information skills, self-efficacy, satisfaction and information use barriers. A standard multiple regression analysis revealed that self-efficacy is a predictor of PHI use behaviour,withstrong and positive unique contributionto PHI use behaviour by about 63% of variance and Beta value of β =.628, followed by demographic factors that had very little and insignificant contribution to the behaviour: income, β = .141 (14%); age, β = -.070 (7%); and education,β = .074 (7%). Test result of the second hypothesis that PHI use skills and self-efficacy motivation intervention could improve PHI use behaviour among teen expectant mothers revealed a substantial main effect for time (pre-test-post-test) Wilk's Lambda =.34 F(2, 27) = 26.59, p<.001, partial eta squared = .66. This implied a positive and significant effect of intervention on the experimental group. However, since the intervention took only 10 weeks (including pre- and post-testing), the study suggests long intervention periods in future research to permit an extensive and intensive examination of PHI use behaviours in maternal communities.This study filled the literature gap on TEMs' information use behaviour patterns and problems through a synthesis of Kari's (2007) Information Outcome model, Fishers' (1996) Information Motivation Behavioural model for intervention, and Bandura's (1987) Social Cognitive Theory on self-efficacy motivation. The study concludes that TEMs should be empowered to apply accurate and relevant information for making informed health choices and decisions that would impact their lifestyle and bring positive pregnancy outcomes. It recommended improvement of ANC education and policy for efficient PHI services and monitoring and effective PHI use among TEMs in the country.